Imagined communities revisited: Asia pacific literature and cultures - Abdul Manaf, Nor Faridah (s.n, 2012)
This research project is a book project which looks at cultures and literatures of the Asia-Pacific region. It looks not only at literary and cultural texts but also cultural performances like Mak Yong, Main Puteri, etc. Other form of expression like the oral tradition, caricature and film are also considered